PRINCIPLES OF DAKWAH IN THE QURAN (Treatment Perspective Of Qs Muhammad Verse19) - Ali Mustafa; Elda Ayumi; Mailin Mailin (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2021)
AbstractGenerally, scholars state that the law of da'wah is obligatory ('ain or kifayah). The problem is, there are opinions that make science a basic condition for preaching. Preaching must be knowledgeable. If that is the case, then how can a Muslim fulfill his duty of preaching? Does he have to wait to memorize and master the Koran 30 juz and thousands of hadiths? What knowledge and in what degree should a preacher master? This paper will answer by making QS Muhammad [47]: 19 as the object of study. Imam Bukhari cited this verse as the main argument in his Sahih when writing the chapter "al-'science of qabl al-qaul wa al-'amal". With a content analysis approach, QS Muhammad [47]: 19 is viewed from five books of interpretation, representing various schools of thought. In conclusion, there are no objections from the five commentators to make QS Muhammad verse 19 a proof of understanding "knowledge before doing good". In fact, three of them strengthen. Therefore, the thesis "science before da'wah" or the science of the conditions for preaching can be accepted as an understanding of "science before doing charity". Based on QS Muhammad [47]: 19, the most standard (basic) knowledge and material in preaching is about la ilaha illallah (tawhid). This verse is also the basis of the four principles of Islamic da'wah and communication, namely divinity, humanity, noble character, and moderation. This finding provides a new perspective in the interpretation of QS Muhammad [47]: 19,Keywords: Knowledge, Da'wah Principles, QS Muhammad Verse 19